Environmental co-benefits and adverse side-effects of alternative power sector decarbonization strategies - Gunnar Luderer (Nature Portfolio, 2019)
There lacks a consistent and holistic evaluation of co-benefits of different mitigation pathways in studies on Integrated Assessment Models. Here the authors quantify environmental co-benefits and adverse side-effects of a portfolio of alternative power sector decarbonisation pathways and show that the scale of co-benefits as well as profiles of adverse side-effects depend strongly on technology choice.